Translating injury prevention evidence into safer padel: Protocol of a TRIPP-guided scoping review - Lennert Goossens; Javier Ramos-Munell; Ana I. Fernandez-de-Osso; José Luis Ceballos-Sánchez (PLoS ONE, 2026)
Padel is a rapidly growing sport with high injury incidence rates and substantial consequences. However, no comprehensive overview exists of the evidence on padel-related injuries and injury prevention strategies. A scoping review can help identify gaps in the emerging field of padel research. The objective of this scoping review is to systematically map the available evidence on padel‑related injuries and injury prevention strategies across all player populations and settings, from epidemiological description to intervention effectiveness. Studies describing injuries or injury risk factors or mechanisms in padel players of any kind and regarding primary injury prevention strategies or interventions involving stakeholders at any socio-ecological level will be considered. Studies that have been conducted in any geographic location, at any playing level, in any setting and in any implementation context will be considered. The proposed scoping review will be conducted in accordance with the JBI methodology for scoping reviews and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) will be followed. A three-step search strategy will be utilized. The search strategy will be adapted for PubMed, SPORTDiscus, Web of Science, Scopus, EMBASE and CINAHL. A structured gray‑literature search will also be conducted. The data extracted from included papers will include specific details about the participants, concept, context, study methods and key findings relevant to the review questions. No critical appraisal of individual sources of evidence will be performed. The extracted data will be presented according to the six stages of the Translating Research into Injury Prevention Practice (TRIPP) framework. The review has been registered through Open Science Framework (osf.io/4t69j).